Pengaruh Orientasi Kewirausahaan dan Pasar terhadap Keunggulan Bersaing dalam Meningkatkan Penjualan pada Usaha Minimarket di Wilayah Cibinong - Nugraha, Widiyanto; Nugroho, Arissetyanto (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The increasingly intense business competition resulting from the implementation of the ASEAN Economic Community (AEC) requires micro-business actors, particularly independent minimarkets in the Cibinong area, to build sustainable competitive advantages in order to maintain and improve their sales performance. This study aims to analyze the influence of entrepreneurial orientation and market orientation on competitive advantage and its impact on sales improvement in minimarket businesses in the Cibinong area. This research employs a quantitative approach with data collection conducted through the distribution of questionnaires based on a Likert scale of 1–5 to 110 respondents consisting of owners and managers of minimarket businesses in the Cibinong area. Sample determination was carried out using the Slovin formula with a margin of error of 10%, while data analysis was performed using path analysis technique with the assistance of SPSS software version 22.0. The results of the study indicate that entrepreneurial orientation has a positive and significant effect on competitive advantage, market orientation has a positive and significant effect on competitive advantage, and competitive advantage has a positive and significant effect on sales improvement. These findings imply that strengthening entrepreneurial orientation through innovation and risk-taking, as well as enhancing market orientation through sensitivity to consumer needs and competitive dynamics, constitute effective strategies for building competitive advantage that ultimately drives sustainable sales growth in minimarket businesses.